2018
DOI: 10.1088/1361-6463/aaf403
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and optimization of Si/BaSi2 heterojunction and BaSi2 homojunction solar cells

Abstract: High light absorption material BaSi2 based heterojunction and homojunctin solar cells were simulated with the program AMPS (analysis of microelectronic and photonic structures)-1D in order to thoroughly understand the mechanism for further improvement in conversion efficiency. Simulation results demonstrated that p+-Si/n-BaSi2 heterojunction solar cells exhibited superior photoelectric performances as compared with n+-Si/p-BaSi2 solar cells. A high conversion efficiency up to of 22.7% were achieved by p+-Si (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…More recently, it has been reported that the orthorhombic barium disilicide (β‐BaSi 2 ) can be applied as the best BSF layer for performance enhancement in CIGS‐based solar cells . The potential of BaSi 2 for solar cell applications has also been reported by many groups …”
Section: Introductionmentioning
confidence: 57%
“…More recently, it has been reported that the orthorhombic barium disilicide (β‐BaSi 2 ) can be applied as the best BSF layer for performance enhancement in CIGS‐based solar cells . The potential of BaSi 2 for solar cell applications has also been reported by many groups …”
Section: Introductionmentioning
confidence: 57%
“…[15][16][17] These properties meet the requirement of high-η thin-film solar cells. Based on the results of such basic research to date, various types of BaSi 2 solar cells have been proposed [18][19][20][21][22][23][24] and fabricated in the form of BaSi 2 /Si, [25][26][27][28][29] BaSi 2 -pn, 30) and n-ZnO/p-BaSi 2 , 31,32) and SnS/BaSi 2 33) by thin-film growth methods such as molecular beam epitaxy (MBE), vacuum evaporation, and sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…[38,39] By positron annihilation spectroscopy, [39] it has been revealed that the electron concentration increases to %10 18 cm À3 with increasing vacancy-type defects [38] when the Ba/Si atomic ratio is far from the stoichiometric ratio. In addition, novel device structures have been proposed, [40][41][42][43][44][45][46][47][48][49][50] and passivation of defects in BaSi 2 has been demonstrated by atomic-hydrogen (H) [51][52][53][54][55][56] and carbon (C) doping. [27,30,57] For deposition techniques, vacuum evaporation of BaSi 2 granules [21][22][23][24][25] and sputtering of BaSi 2 targets [26][27][28][29][30] or cosputtering of Si and Ba targets [31] are suitable to form BaSi 2 films for large-scale deployment on inexpensive substrates like SiO 2 .…”
Section: Introductionmentioning
confidence: 99%